MILK: a Python scripting interface to MAUD for automation of Rietveld analysis - Savage, Daniel J.; Lutterotti, Luca; Biwer, Christopher M.; McKerns, Michael; Bolme, Cynthia; Knezevic, Marko; Vogel, Sven C. (Journal of applied crystallography, 2023)
Modern diffraction experiments (e.g. in situ parametric studies) present scientists with many diffraction patterns to analyze. Interactive analyses via graphical user interfaces tend to slow down obtaining quantitative results such as lattice parameters and phase fractions. Furthermore, Rietveld refinement strategies (i.e. the parameter turn‐on‐off sequences) tend to be instrument specific or even specific to a given dataset, such that selection of strategies can become a bottleneck for efficient data analysis. Managing multi‐histogram datasets such as from multi‐bank neutron diffractometers or caked 2D synchrotron data presents additional challenges due to the large number of histogram‐specific parameters. To overcome these challenges in the Rietveld software Material Analysis Using Diffraction (MAUD), the MAUD Interface Language Kit (MILK) is developed along with an updated text batch interface for MAUD. The open‐source software MILK is computer‐platform independent and is packaged as a Python library that interfaces with MAUD. Using MILK, model selection (e.g. various texture or peak‐broadening models), Rietveld parameter manipulation and distributed parallel batch computing can be performed through a high‐level Python interface. A high‐level interface enables analysis workflows to be easily programmed, shared and applied to large datasets, and external tools to be integrated with MAUD. Through modification to the MAUD batch interface, plot and data exports have been improved. The resulting hierarchical folders from Rietveld refinements with MILK are compatible with Cinema: Debye–Scherrer, a tool for visualizing and inspecting the results of multi‐parameter analyses of large quantities of diffraction data. In this manuscript, the combined Python scripting and visualization capability of MILK is demonstrated with a quantitative texture and phase analysis of data collected at the HIPPO neutron diffractometer. The MAUD Interface Language Kit (MILK) provides a Python interface to the Rietveld software MAUD, enabling scriptable refinements. The MILK framework includes parallel computing and folder management which enable high‐throughput Rietveld analysis, visualization and validation.